"Prisoner Never Gave Me Anything for What He Done:" Aboriginal Voices in the Criminal Court - Gavigan, Shelley A. M. (Osgoode Digital Commons, 2007)
Aboriginal people participated in different ways in the criminal process in the earl years of the North- West Territories region of Canada, including, as accused persons, as Informants, and as witnesses. Their participation was often mediated by the police, Indian agents and sometimes their Chiefs. Their word were also mediated by interpreters, both linguistic and cultural and their signatures were invariably marked as "X" on their depositions. Scholarship that has examined the relationship of Aboriginal peoples to the criminal law has tended to interrogate the criminalization and moral regulation strategies implicit in the process of colonization and domination of the First Peoples. This paper will discuss less visible aspects of the legalized processes of colonization: (I) the particpation of Plains Cree, Saulteaux and Metis peoples, among others, whose traditional values and norms nonetheless seep through the handwritten, translated transm2tion andalien norms of the Canadian criminal court, and, (2) cases in which Aboriginal complainants who, notwithstanding their substantive inequalig invoked the criminal process to insist that those who wronged them also be punished in accordance with the principles of Canadian law.